Regulating a multiproduct and multitype monopolist - Dezsö Szalay (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
I study the optimal regulation of a firm producing two goods. The firm has private information about its cost of producing either of the goods. I explore the ways in which the optimal allocation differs from its one dimensional counterpart. With binding constraints in both dimensions, the allocation involves distortions for the most efficient producers and features overproduction for some less efficient types.
urn:nbn:de:bvb:19-epub-14770-0
Keywords: D82; L21; 330